Mobile GIS and local knowledge in monitoring carbon stocks - Verplanke, Jeroen (Technical Centre for Agricultural and Rural Cooperation, 2005)
Jeroen Verplanke describes the development of a mobile GIS unit that can be used by local communities to record and monitor the carbon stored in natural forests.